«Репетиции смерти» в стихотворениях “Блюз беженцев» У.Х. Одена и «Беженцы» Р. Джаррелла (к вопросу осмысления проблемы беженцев в американской поззии о второй мировой войне) - Никифоров, А. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the best American poems devoted to refugees of the world war II. The comparative analyses based on the thematic and stylistic similarity was carried out. Various forms of the main artistic device – repetition – were studied.